Aspirin has limited ability to modulate shear-mediated platelet activation associated with elevated shear stress of ventricular assist devices. Issue 140 (April 2016) - Valerio, Lorenzo; Tran, Phat L.; Sheriff, Jawaad; Brengle, William; Ghosh, Ram; Chiu, Wei-Che; Redaelli, Alberto; Fiore, Gianfranco B.; Pappalardo, Federico; Bluestein, Danny; Slepian, Marvin J.
Abstract: Continuous flow ventricular assist devices (cfVADs) while effective in advanced heart failure, remain plagued by thrombosis related to abnormal flows and elevated shear stress. To limit cfVAD thrombosis, patients utilize complex anti-thrombotic regimens built upon a foundation of aspirin (ASA). While much data exists on ASA as a modulator of biochemically-mediated platelet activation, limited data exists as to the efficacy of ASA as a means of limiting shear-mediated platelet activation, particularly under elevated shear stress common within cfVADs. We investigated the ability of ASA (20, 25 and 125 μM) to limit shear-mediated platelet activation under conditions of: 1) constant shear stress (30 dynes/cm 2 and 70 dynes/cm 2 ); 2) dynamic shear stress, and 3) initial high shear exposure (70 dynes/cm 2 ) followed by low shear exposure – i.e. a platelet sensitization protocol, utilizing a hemodynamic shearing device providing uniform shear stress in vitro . The efficacy of ASA to limit platelet activation mediated via passage through a clinical cfVAD system (DeBakey Micromed) in vitro was also studied. ASA reduced platelet activation only under conditions of low shear stress (38% reduction compared to control, n = 10, p  < 0.004), with minimal protection at higher shear stress and under dynamic conditions (n = 10, p  > 0.5) with no limitation of platelet sensitization. ASA had limited ability (25.6% reduction in platelet activation rate) to modulate shear-mediated platelet activation induced via cfVAD passage. These findings, while performed under "deconstructed" non-clinical conditions by utilizing purified platelets alone in vitro, provide a potential contributory mechanistic explanation for the persistent thrombosis rates experienced clinically in cfVAD patients despite ASA therapy. An opportunity exists to develop enhanced pharmacologic strategies to limit shear-mediated platelet activation at elevated shear levels associated with mechanical circulatory support devices. Highlights: ASA has limited efficacy in modulating high shear-mediated platelet activation (SMPA). ASA is unable to limit shear-mediated platelet sensitization. ASA has limited efficacy in modulating SMPA for shear associated with cfVADs. Need exists for strategies to modulate SMPA with "hypershear" (600–1000 dynes/cm 2 ).